-6-11b=-7b+6

Simple and best practice solution for -6-11b=-7b+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6-11b=-7b+6 equation:



-6-11b=-7b+6
We move all terms to the left:
-6-11b-(-7b+6)=0
We get rid of parentheses
-11b+7b-6-6=0
We add all the numbers together, and all the variables
-4b-12=0
We move all terms containing b to the left, all other terms to the right
-4b=12
b=12/-4
b=-3

See similar equations:

| 1/6(x-36)=5+2x | | -4j+7=-1−4j | | 8n+5=5+8n | | 20y=–4+18y | | 17p=16p-16 | | -3−4p=-4p−9 | | v–20=-29 | | -x-8=−4x−23 | | 9.5y=-95 | | 11(-2x+6)-5=61 | | 5v-13v=16 | | 7t−7t=0 | | -3(-4x+2)-9=45 | | -26=7(4z=9 | | 7=a+9 | | 8(2x-1)+7=-33 | | -3u−3=1−5u | | -7+9n=9n | | 17w−8w=18 | | 4x+34=7x | | 12x-5+8x+10=-55 | | 2=z-2/3 | | -42-6m=12m | | 187=108-x | | 1=-v/5 | | -12h=-6-18h | | -7x+4-10x+3=24 | | (3/7)x=66 | | 3−6f=-6f+3 | | 2(x+1)=54 | | -6j−4=-5j+4 | | -10y+10=-7+7y |

Equations solver categories